Smart antennas - Godara, Lal Chand, ....- (Boca Raton : CRC, 2004)
Samenvatting:The use of smart antennas to increase mobile communications channels hasre-ignited research and development in the field. Practicing engineersare eager to discover more about this subject, and need a comprehensivebook that can provide a learning platform and prevent the loss of timespent on searches through journal literature.Smart Antennas examinesnearly all aspects of array signal processing and presents them in alogical manner. It delivers a detailed treatment of antenna arrayprocessing schemes, adaptive algorithms to adjust weighting, direction ofarrival (DOA) estimation methods, diversity-combining methods that combatfading and reduce errors.The book introduces the various processorstructures suitable for the narrowband field, examining the behavior ofboth element space and beamspace processors. It then explores adaptiveprocessing, focusing on the simple matrix inversion algorithm,constrained least mean squares (LMS), the neural network approach, andmore. The text also describes smart antennas that are suitable forbroadband signals, and presents analyses and techniques suitable forcorrelated fields in narrowband and broadband signals.This volumesupplements its content with extensive references, enabling you tofurther investigate smart antenna array schemes and application.
Keywords: Antennes